Perbanyakan Tanaman Jeruk Siam (Citrus nobilis L.) dengan Teknik Kultur in vitro Menggunakan Biji Tanaman Terinfeksi Penyakit Citrus Vein Phloem Degeneration (CVPD) - BAYU ARYA BAGASKARA; I GEDE PUTU WIRAWAN; MADE SRITAMIN; I GUSTI AYU DIAH YUNITI (Agrotrop : Journal on Agriculture Science, 2018)
Citrus (Citrus nobilis L.) Propagation Through Culture In Vitro Using Seed From Infected Plants Of Citrus Vein Phloem Degeneration (CVPD) Disease. The sample was taken in Belancan Village, Kintamani District, Bangli Regency, and invitro culture was conducted in UPT. Genetics Resource and Molecular Biology Laboratory in February to June 2018. This research purposes were to get the new citrus plant from citrus seed infected of CVPD disease explants with culture in vitro and found the presence of the bacterium Liberobacter asiaticus in results of citrus plants culture in vitro. The sampling method is using plants appearance. Obtained sample 1 is a plant that shows severe symptoms of CVPD disease and sample 2 plants that show no symptoms of CVPD disease. Seed Sample is cultured with MS0 medium for 8 WAP then proceed to acclimatization. The results of this research showed that the seed explants from both samples were able to grow well and did not have the characteristic of CVPD disease, but explant seed sample 2 in vitro culture result showed that the bacterial DNA bacterium Liberobacter asiaticus pathogen CVPD disease does exist in length 1160bp, so it cannot be expected to produce CVPD-free crops.